Respuesta :

Answer:

10

Step-by-step explantion

Simplifying

2x + 3 + 25 = 3x + -17

Reorder the terms:

3 + 25 + 2x = 3x + -17

Combine like terms: 3 + 25 = 28

28 + 2x = 3x + -17

Reorder the terms:

28 + 2x = -17 + 3x

Solving

28 + 2x = -17 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.

28 + 2x + -3x = -17 + 3x + -3x

Combine like terms: 2x + -3x = -1x

28 + -1x = -17 + 3x + -3x

Combine like terms: 3x + -3x = 0

28 + -1x = -17 + 0

28 + -1x = -17

Add '-28' to each side of the equation.

28 + -28 + -1x = -17 + -28

Combine like terms: 28 + -28 = 0

0 + -1x = -17 + -28

-1x = -17 + -28

Combine like terms: -17 + -28 = -45

-1x = -45

Divide each side by '-1'.

x = 45

Simplifying

x = 45

Answer:

  • x = 45

Step-by-step explanation:

Exterior angle is same as sum of two remote interior angles:

  • 2x + 3 + 25 = 3x - 17
  • 2x + 28 = 3x - 17
  • 3x - 2x = 28 + 17
  • x = 45